Clostridium difficile genotypes in piglet populations in Germany - Schneeberg, Alexander; Neubauer, Heinrich; Schmoock, Gernot; Baier, Sylvia; Harlizius, Jürgen; Nienhoff, Hendrik; Brase, Katja; Zimmermann, Stefan; Seyboldt, Christian (Journal of clinical microbiology, 2013)
Clostridium difficile was isolated from 147 of 201 (73%) rectal swabs of piglets from 15 farms of Lower Saxony and North Rhine-Westphalia. In 14 farms, 14 to 100% (mean, 78%) of the animals tested were culture positive. The rate of isolation was 68% postpartum, increased to 94% in animals 2 to 14 days of age, and declined to 0% for animals 49 days of age and older. There was no link between isolation and antibiotic treatment or diarrhea of piglets. Strains were assigned to 10 PCR ribotypes, and up to 4 PCR ribotypes were found to be present at the same time on a farm. The closely related PCR ribotypes 078 (55%) and 126 (20%) were most frequently recovered and were present in 13 of the 14 positive farms. The comparison of multilocus VNTR (variable number of tandem repeats) analysis (MLVA) data from this study and previously published data on human, porcine, and bovine PCR ribotype 078 isolates from 5 European countries revealed genetic differences between strains of different geographic origin and confirmed the relatedness of human and porcine C. difficile isolates. This study demonstrated that the human-pathogenic PCR ribotypes 078 and 126 are predominant in piglets in Germany. The results suggest that presence of C. difficile is correlated with animal age but not with antibiotic treatment or clinical disease. MLVA indicated that strains of the same geographical origin are often genetically related and corroborated the hypothesis of a close epidemiological connection between human and porcine C. difficile isolates.
Gesehen am 12.07.2021